Mitochondrial dysfunction in cardiovascular disease: Towards exercise regulation of mitochondrial function - Li, Kunzhe; Wan, Bingzhi; Li, Sujuan; Chen, Zhixin; Jia, Hao; Song, Yinping; Zhang, Jiamin; Ju, Wenyu; Ma, Han; Wang, Youhua (Frontiers in Physiology, 2023)
The morbidity and mortality of cardiovascular diseases are exceedingly high worldwide. Pathological heart remodeling, which is developed as a result of mitochondrial dysfunction, could ultimately drive heart failure. More recent research target exercise modulation of mitochondrial dysfunction to improve heart failure. Therefore, finding practical treatment goals and exercise programs to improve cardiovascular disease is instrumental. Better treatment options are available with the recent development of exercise and drug therapy. This paper summarizes pathological states of abnormal mitochondrial function and intervention strategies for exercise therapy.